2016
DOI: 10.1001/jamaoto.2016.1954
|View full text |Cite
|
Sign up to set email alerts
|

Association of Intraoperative Neuromonitoring With Reduced Recurrent Laryngeal Nerve Injury in Patients Undergoing Total Thyroidectomy

Abstract: Our findings showed that the use of IONM decreased significantly both temporary and permanent RLN injuries. The technology of IONM is safe and reliable, and this technique is an important adjunct in nerve dissection and functional neural integrity. The routine use of IONM reduced pitfalls and provided guidance for our surgeons in difficult cases, reoperations, and high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
60
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 27 publications
(19 reference statements)
6
60
1
Order By: Relevance
“…Furthermore, surgical techniques have improved considerably over the nearly four decades this database spans with, for example, the advent of intraoperative neuromonitoring. 18 Nonetheless, these results depict a "real world value" across the board of healthcare over >30 years and thereby support the current view that thyroidectomy should in fact only be performed in top level centres by high level surgeons.…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, surgical techniques have improved considerably over the nearly four decades this database spans with, for example, the advent of intraoperative neuromonitoring. 18 Nonetheless, these results depict a "real world value" across the board of healthcare over >30 years and thereby support the current view that thyroidectomy should in fact only be performed in top level centres by high level surgeons.…”
Section: Discussionsupporting
confidence: 70%
“…Despite the rate being very low in the present day due to a better operative technique (40,41), it is better to avoid this problem. Inabnet et al (34), Dionigi et al (36), and Wang et al (33) demonstrated intraoperative neuromonitoring in TOETVA operations with good results.…”
Section: Discussionmentioning
confidence: 96%
“…The routine use of IONM in thyroid surgery is controversial. Existing data do not support that the routine use of IONM reduces the rate of RLN damage . IONM, however, may be beneficial in procedures that are either high risk or performed by low‐volume surgeons .…”
Section: Discussionmentioning
confidence: 99%